(untitled) (Journal of Dhaka Medical College, 2011)
Context: Genital prolapse is a very common gynaecological disorder in Bangladesh. But women do not admit this problem due to shame, ignorance, social taboo and insolvency. The rural scenario is much more disastrous. The aim of the present study was to find out the prevalence of genital prolapse and its correlation with sociodemographic status in a rural area of Bangladesh. Methods: A cross-sectional descriptive type of study was conducted at a village named Sharifbag of Dhamrai upazilla under Dhaka district from March to May in the year 1997. The total population of the village was 2605. All the married women of reproductive age (15-49 years) of that village were the study population. The sample size was estimated 200. They were interviewed based upon a semi-structured questionnaire set in Bengali language. After collection, data were compiled, summarized and analyzed to get the results. Results: Among 200 women, only 9 were reported to have the complaints of a genital prolapse. 54% of women were in 15-29 years age group, while 46% belonged to 30-49 years age group. Most of the women were married (86%) and having no education (78.5%). The present study revealed that respondents’ age had no association with the incidence of genital prolapse (p>0.05). But strong association was found between number of child and genital polapse (p<0.05). Besides, respondents’ monthly income was also strongly associated with incidence of genital polapse (p<0.05). More incidence of genital polapse was found in women having parity >6 and 5-6 and hailing from a very low income group. Key words: Genital prolapse; sociodemographic status; rural community; reproductive health. DOI: 10.3329/jdmc.v19i2.7082 J Dhaka Med Coll. 2010; 19(2) : 118-121